(untitled) (Global Journal of Science Frontier Research, 2022)
A field experiment in a randomized block design was conducted during Rabi season 2019-2020 on 13 wheat varieties with the twin objectives of objectively selecting and precisely recommending the suitable plant types to farmers of Deoria district in eastern Uttar Pradesh. The varieties were evaluated on 12 characters likeplant height (cm), flag leaf area (cm 2 ), peduncle length (cm), spike length (cm), effective tillers, grains per spike (grain number), grain weight (g), spikelets per spike, test weight (g), grain yield per plant (g), biological yield per plant (g) and harvest index (%). Normalized cumulative ranks were used to objectively select suitable crop ideotypes. The top five varieties viz., HD-2967, MACS-6222, HUW-669, K-0307 and HUW-213 were precisely recommended to farmers of this region for cultivation.